Preparation of SrAl2O4:Eu2+, Dy3+ phosphors using propylene oxide as gel agent and its optical properties. (4th January 2018) - Yang, Yuting; Jiang, Hongyi; Xu, Dong; Hai, Ou; Yang, Ting
Abstract: The SrAl2 O4 :Eu 2+, Dy 3+ phosphors were prepared by sol–gel method using propylene oxide as gel agent. The precursors and phosphors were characterized by multiple techniques including Fourier-transform infrared spectroscopy, x-ray diffraction, scanning electron microscopy, fluorescence spectrometer, long afterglow material optical test system, etc. The results indicate that the excitation and emission spectra intensity of phosphors firstly increase and then decrease with the addition of propylene oxide, and sample S3 reach maximum value. The maximum initial brightness can reach 7.28 cd m −2, and the afterglow time achieve to 253 min, but the initial brightness, afterglow time and decay rate are always declining. These phenomena can be explained on the basis of sample's crystallization property, the change of aggregates size and increase of liquid phase content. What's more, this sol–gel method is more advantageous than traditional sol–gel method of NH4 HCO3 as gel agent, not only because the gel time is adjustable, but also the afterglow performance is enhanced remarkably.